Interlocking directorates & corporate governance - Egwuonwu, Ronald (Lagos; Strides Associates Ltd., 1997)
The book presents fundamental concepts of corporate governance with particular focus on the Nigerian scene, with appropriate illustration of practical corporate governance in some businesses in the country.
Published to honour Sir Gabriel Osawaru Igbinedion. for purposeful corporate governance and excellent entrepreneur initiaives.
Includes bibliographical references, index
osc 19/8/16
Loans
Keywords: Corporate governance; Interlocking directorates; Directors